1997
DOI: 10.1097/00005392-199709000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preservation Induced Reperfusion Injury via Intraoperative Renal Transplant Blood Flow and Endothelin Concentration Studies

Abstract: Vasoactive factors other than endothelin most likely contribute to reperfusion injury. Furthermore, the ultrasonic transit time flow probe accurately measures post-reperfusion renal blood flow and offers a practical method for assessing acute reperfusion injury, which may help to optimize immunosuppressive strategies to decrease allograft loss associated with delayed graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
2
1
0
2
Order By: Relevance
“…Consequently, the 60:2 min perfusion ratio was greater in the Tx-2hr than in the Tx16hr group (table 2). These findings were consistent with the results of Bretan et al [28] who suggested that the 60:5-min postreperfusion RBF ratio is a prognostic indicator of subsequent renal function in humans.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, the 60:2 min perfusion ratio was greater in the Tx-2hr than in the Tx16hr group (table 2). These findings were consistent with the results of Bretan et al [28] who suggested that the 60:5-min postreperfusion RBF ratio is a prognostic indicator of subsequent renal function in humans.…”
Section: Discussionsupporting
confidence: 93%
“…However recent studies have shown that it is involved in various diseases [2], especially in renal failure [3][4][5][6]. In addition, ET-1 has an important role in acute rejection after renal transplantation [7]. We confirmed that ET-1 increases just before rejection and decreases after graft function is improved by immunosuppressive treatment [8].…”
Section: Introductionsupporting
confidence: 72%
“…La disfunción inicial del injerto renal trasplantado procedente de donante vivo se ha cifrado entre el 5% y el 10%, independientemente de la técnica de extracción. Esta disfunción, definida por la necesidad de diálisis durante la primera semana post-trasplante, parece que se asocia a un mayor riesgo de rechazo agudo y crónico que condicionaría una menor supervivencia del injerto 10 .…”
Section: Discussionunclassified